Growth Performance of Larvae Produced from Vitamin E Treated Female Clarias batrachus (Linnaeus) (Progressive Agriculture, 2013)
An experiment to observe the growth performance of the larvae produced from female Clarias batrachus treated with 4 dietary levels of vitamin E viz. 0 mg, 50 mg, 100 mg, and 200 mg /kg feed was conducted for 28 days. After rearing for 3 months females were used for induction of breeding to produce larvae. Same dose of pituitary gland (100 mg PG/kg body weight) was used for all treatments. From the 7th day of hatching, the larvae were reared for another period of 28 days to see growth and survival rate of the larvae produced by the broods maintained under different dietary levels of vitamin E. In case of growth performance (percent length gain, percent weight gain, specific growth rate) and health condition larvae of T2 (50 mg vitamin E/kg feed) showed significantly better result when compared with those of T1 and T3. There was no significant difference in the growth performance between the larvae of T2 and T4. Larvae of T2 although showed higher survival rate but the difference between different treatments was insignificant. The results concluded that 50 mg vitamin E/kg feed is more suitable to increase growth and survival rate of the larvae.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16862 Progress. Agric. 20(1 & 2): 107 116, 2009